Developments of International Trade Theory - Negishi, Takashi. (Advances in Japanese Business and Economics, 2014)
Developments of International Trade Theory offers the life-long reflections of a distinguished Japanese scholar who pioneered the application of general equilibrium theory to international trade. Written in a style that makes it easily accessible to scholars and students, the book combines standard topics on international trade with a discussion of the evolution of the theory and as well as recent discussions on topics such as immiserizing growth.   This book consists of two parts. Part I examines the historical progression of international trade theory, and Part II addresses the modern theory and recent developments of international trade. In this way the book offers a comprehensive evaluation of the non-monetary problems of international economics. Taking advantage of the publication of this new edition, the author includes two new chapters, “Adam Smith and Disequilibrium Economic Theory” and “Complete Specialization in Classical Economics,” which readers will profit from reading after they have studied the basic theories of international trade in the main part of the book.